An investigation into student and qualified physiotherapists description of lung sounds - Russell Mayne; Amanda Gossip; Chris Rodseth (AOSIS, 1997)
The ability to accurately describe lung sounds were tested on 146 subjects (qualified physiotherapists from a tertiary care hospital and third, and fourth year students from three universities). The effect of increased clinical time as well as the nomenclature used was also investigated. The subjects had to recognise six tape recorded lung sounds on a multiple-choice answer sheet. It was found that in total the subjects were minimally accurate with a median score of three out of six. The relationship between increasing clinical time and increasing accuracy in determining lung sounds were not significant. Significance was set at p < 0.05. Comparing third and forth years a p value of 0.0639 was found, while a p value 0.3592 was found when comparing forth years and qualified physiotherapists. Mean scores did however seem to indicate a trend, as they increased with increasing clinical time. The "Forgacs" nomenclature was used by the majority of subjects tested.